Analisis Manajemen Organisasi Dalam Pengawasan Perbankan Syariah Di Indonesia - Nisa, Isnaini Maulidatu (Jurnal Ilmiah Ekonomi Islam, 2024)
Islamic banking is a financial institution whose operational system must be supervised by several supervisory boards. The management of Islamic banking supervisory organizations has three parts, DSN and DPS, Management Information Systems, and Internal Audit. This research uses the literature approach method. The purpose of this research is to find out the supervision in Islamic banking in Indonesia. The organizational structure of Islamic banking consists of the National Sharia Council (DSN) whose role is to provide fatwas and supervise Islamic banking products to comply with sharia principles. Then there is the Sharia Supervisory Board (DPS) whose role is to oversee the implementation of DSN decisions in Islamic financial institutions. In addition, the role of management information systems and internal audit in supporting Islamic banking operations is discussed. This study aims to determine organizational management, especially supervision carried out by DSN and DPS to ensure that Islamic banking operations run in accordance with sharia principles.